2008
DOI: 10.1111/j.1462-2920.2008.01654.x
|View full text |Cite
|
Sign up to set email alerts
|

Gradients of coastal fish farm effluents and their effect on coral reef microbes

Abstract: Coastal milkfish (Chanos chanos) farming may be a source of organic matter enrichment for coral reefs in Bolinao, Republic of the Philippines. Interactions among microbial communities associated with the water column, corals and milkfish feces can provide insight into the ecosystem's response to enrichment. Samples were collected at sites along a transect that extended from suspended milkfish pens into the coral reef. Water was characterized by steep gradients in the concentrations of dissolved organic carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 66 publications
2
59
0
Order By: Relevance
“…We conclude that the spawned material is patchily distributed in particulate form in the surface waters of the lagoon until it sinks or is advected out of the system. Interestingly, the concentrations of TOC at both sites during spawn and nonspawn conditions were similar in magnitude to dissolved organic carbon concentrations in the North Pacific Subtropical Gyre, as well as pristine coral reef atolls (Church et al 2002, Dinsdale et al 2008, and were less than dissolved organic carbon concentrations found at more anthropogenically impacted coral reef environments (Garren et al 2008, Rochelle-Newall et al 2008. While Kaneohe Bay routinely receives input from streams originating from the surrounding urban terrain, the stable and relatively low concentrations of TOC present at the lagoon and reef flat sampling sites indicate that the terrestrial input of organic carbon may not reach all environments within Kaneohe Bay, or else it is rapidly diluted or advected after highly episodic input (i.e.…”
Section: Pelagic Microbial Response To Coral Spawning Eventsmentioning
confidence: 75%
See 1 more Smart Citation
“…We conclude that the spawned material is patchily distributed in particulate form in the surface waters of the lagoon until it sinks or is advected out of the system. Interestingly, the concentrations of TOC at both sites during spawn and nonspawn conditions were similar in magnitude to dissolved organic carbon concentrations in the North Pacific Subtropical Gyre, as well as pristine coral reef atolls (Church et al 2002, Dinsdale et al 2008, and were less than dissolved organic carbon concentrations found at more anthropogenically impacted coral reef environments (Garren et al 2008, Rochelle-Newall et al 2008. While Kaneohe Bay routinely receives input from streams originating from the surrounding urban terrain, the stable and relatively low concentrations of TOC present at the lagoon and reef flat sampling sites indicate that the terrestrial input of organic carbon may not reach all environments within Kaneohe Bay, or else it is rapidly diluted or advected after highly episodic input (i.e.…”
Section: Pelagic Microbial Response To Coral Spawning Eventsmentioning
confidence: 75%
“…Recent research has focused on characterizing coral-associated bacterial and archaeal communities with the goals of assessing community diversity, species-specificity and the potential roles played by the microorganisms in the health of corals (Rohwer et al 2001, Kellogg 2004, Beleneva et al 2005, Bourne 2005, Bourne & Munn 2005, Guppy & Bythell 2006, Sekar et al 2006, Lesser et al 2007). However, planktonic marine microorganisms may also significantly affect the health of corals and reef ecosystems, though their characterization has received considerably less attention (Dinsdale et al 2008, Garren et al 2008. For example, blooms of potentially pathogenic microorganisms that are not typically dominant mem-bers of the microbial community have emerged following nutrient loading in subtropical coastal areas (Piccini et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, marine roseobacters represent a diverse group of bacteria that possess a variety of physiologies and have been previously found in internal associations with developing P. meandrina (6) and Porites astreoides (51). Members of the Roseobacter clade also frequently form relationships with adult corals (14,16,21,23,24,30,33,48,54,55), but it is unclear how this specificity translates into homogeneous or heterogeneous roles within the coral holo- biont. Members of this important group of marine bacteria are known to perform a variety of distinct functions (12,37), including the consumption of the organic sulfur metabolite dimethylsulfoniopropionate, which is abundantly secreted by coral zooxanthellae (11,18), and the production of probiotic compounds (33,49).…”
Section: Discussionmentioning
confidence: 99%
“…data). A recent semi-quantitative comparison of bacterial genetic markers from the fish farming area of Bolinao Bay and nearby coral reefs has already suggested a 'wash-out' of certain bacteria, predominantly Vibrio spp., from the fish cages to the coral reefs (Garren et al 2008). …”
mentioning
confidence: 99%